1997
DOI: 10.1016/s0886-3350(97)80081-8
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber contamination during cataract surgery with intraocular lens implantation

Abstract: Bacteria entered the anterior chamber during cataract extraction and remained there at the end of surgery in a significant percentage of patients. Surgical technique, preoperative antibiotics, and preoperative lacrimal system irrigation had no statistically significant effect on contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 19 publications
3
45
1
7
Order By: Relevance
“…In fact, the current culture media for isolating conjunctival bacteria described in Chapter 1 21 is different from that in the Khorazo et al studies 3 mentioned in Chapter 24 of the same volume, in the same book 21 (revised 10 years before). In more recent studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] most samples of patients undergoing cataract surgery have a small size and the frequency of the isolated bacteria varies a lot between them due to different factors 18 (the isolating culture media used, the exclusion criteria used to select the patients and the geographical area where they lived). Among these factors the climatic conditions in Madrid have been statistically associated with the conjunctival bacteria frequency of our patients undergoing cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the current culture media for isolating conjunctival bacteria described in Chapter 1 21 is different from that in the Khorazo et al studies 3 mentioned in Chapter 24 of the same volume, in the same book 21 (revised 10 years before). In more recent studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] most samples of patients undergoing cataract surgery have a small size and the frequency of the isolated bacteria varies a lot between them due to different factors 18 (the isolating culture media used, the exclusion criteria used to select the patients and the geographical area where they lived). Among these factors the climatic conditions in Madrid have been statistically associated with the conjunctival bacteria frequency of our patients undergoing cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Subconjunctival cefuroxime achieves therapeutic levels in the anterior chamber within 12-24 min of administration and maintains clinically significant levels for up to 12 h. 17,18 Postoperative therapeutic antibiotic levels within the anterior chamber will help to counteract the potential bacterial load in the eye as bacteria are present in the anterior chamber at the end of cataract surgery in 13-43% of patients. [19][20][21] There are some limitations to this study. Case ascertainment was questionnaire-based and dependent on voluntary reporting by ophthalmologists throughout the UK.…”
Section: Discussionmentioning
confidence: 98%
“…The seed stock of the Piry virus, strain BeAn 41191 (LD 50 =10 8,5 ), was obtained from the brain macerates of an infected mice.…”
Section: Methodsmentioning
confidence: 99%
“…This increase has occurred si contaminates the aspiration fluid (13) . Contamination of the aspiration fluid may seem normal to a certain extent because it has been shown that during and at the conclusion of intraocular operations, bacteria are present on the conjunctiva and in the anterior chamber (4,5) . It has been suspected that reflux from the internal tubing repre sented a potential source of endophthalmitis, but outflow lines have not been investigated.…”
Section: Introductionmentioning
confidence: 99%